CORRELATION AND PATH ANALYSIS ON PHENOTYPIC CHARACTERS OF DOUBLED HAPLOID RICE LINES - Heni Safitri; Bambanng S. Purwoko; Iswari S. Dewi; Buang Abdullah (Widyariset, 2011)
Grain yield improvement is the main objective in rice breeding programs. The objective of this study was to determine the phenotypic characters that have a direct or indirect effect on grain yield of double haploid lines. It expected can be used as selection criteria. The study was conducted on August 2009 at Cikeumeuh Bogor using randomized block design (RBD) with three replications. The materials used were 33 doubled haploid rice lines and three varieties/landraces rice. The results showed that number of productive tillers per hill, number of grains per panicle and 1,000 grain weight of rice can be used as selection criteria in improving grain yield. These three characters has a positive and very signiﬁ cant correlation, positive and high direct effect on grain yield, and havea high heritability value.